Art Studies in the Context of Power Relations in Lithuania, 1940–1953: The Case of the Activities and Closure of Kaunas Applied and Decorative Art Institute - Žukienė Rasa (Sciendo, 2021)
The main purpose of this report is to discuss the influence of political power on art studies in Lithuania and the creative work of artists from 1940 to 1953. It will be based on the destruction of the Kaunas Institute of Applied and Decorative Arts, which is little known to art historians. After the Second World War, this institute actually followed the traditions of Kaunas Art School (1922–1940): that was the reason for its closure in 1951. The closure was officially called the reorganisation and continuation of art studies in Vilnius.